Vitamin D Deficiency Is Associated with Increased Osteocalcin Levels in Acute Aortic Dissection: A Pilot Study on Elderly Patients - Elena Vianello; Elena Dozio; Alessandra Barassi; Lorenza Tacchini; John Lamont; Santi Trimarchi; Massimiliano M. Marrocco-Trischitta; Massimiliano M. Corsi Romanelli (Hindawi Limited, 2017)
An imbalance between degradation and reconstruction of the aortic wall is one of the leading causes of acute aortic dissection (AAD). Vitamin D seems an intriguing molecule to explore in the field of AAD since it improves endothelial function and protects smooth muscle cells from inflammation-induced remodeling, calcification, and loss of function, all events which are strongly related to the aging process. We quantified 25-hydroxy vitamin D, calcium, parathormone, bone alkaline phosphatase, and osteocalcin levels in 24 elderly AAD patients to identify a potential pathological implication of these molecules in AAD. Median 25-hydroxy vitamin D (10.75 ng/mL, 25th-75th percentiles: 6.86-19.23 ng/mL) and calcium levels (8.70 mg/dL, 25th-75th percentiles: 7.30-8.80 mg/dL) suggested hypovitaminosis D and a moderate hypocalcemia. Thirty-eight percent of AAD patients had severe (<10 ng/mL), 38% moderate (10-20 ng/mL), and 24% mild 25-hydroxy vitamin D deficiency (20-30 ng/mL). A significant inverse correlation was observed between 25OHD and osteocalcin levels. All the other molecules were unchanged. A condition of hypovitaminosis D associated to an increase in osteocalcin levels is present in AAD patients. The identification of these molecules as new factors involved in AAD may be helpful to identify individuals at high risk as well to study preventing strategies.